Interprofessional education in cardiothoracic surgery: a narrative review - Lampridis, Savvas; Scarci, Marco; Cerfolio, Robert J. (Frontiers in Surgery, 2024)
Interprofessional education, an approach where healthcare professionals from various disciplines learn with, from, and about each other, is widely recognized as an important strategy for improving collaborative practice and patient outcomes. This narrative review explores the current state and future directions of interprofessional education in cardiothoracic surgery. We conducted a literature search using the PubMed, Scopus, and Web of Science databases, focusing on English-language articles published after 2000. Our qualitative synthesis identified key themes related to interprofessional education interventions, outcomes, and challenges. The integration of interprofessional education in cardiothoracic surgery training programs varies across regions, with a common focus on teamwork and interpersonal communication. Simulation-based training has emerged as a leading modality for cultivating these skills in multidisciplinary settings, with studies showing improvements in team performance, crisis management, and patient safety. However, significant hurdles remain, including professional socialization, hierarchies, stereotypes, resistance to role expansion, and logistical constraints. Future efforts in this field should prioritize deeper curricular integration, continuous faculty development, strong leadership support, robust outcome evaluation, and sustained political and financial commitment. The integration of interprofessional education in cardiothoracic surgery offers considerable potential for enhancing patient care quality, but realizing this vision requires a multifaceted approach. This approach must address individual, organizational, and systemic factors to build an evidence-based framework for implementation.